Triple Bottom Line Optimization for Sustainable Product Design - Zahari, Taha; H. A., Salaam; Tuan Mohammad Yusoff, Tuan Ya (2015)
The triple bottom line concept is based on the evaluation of three criteria namely financial profitability, environmental integrity and social equity. Consideration of the financial profitability is critical in ensuring the economic sustainability. Environmental integrity considerations have become very crucial as the world communities have realized the necessity to meet the needs of the present generations without compromising the ability of future generations to meet their own needs. Social equity is difficult to identify but at the factory floor level it could imply the impact of manufacturing a product on workers health. In this paper the concept is applied in the manufacturing phase of a product taking into consideration the impact of the design on economics, environmental divided into energy consumed and carbon footprint and ergonomics effect. However it involves multi criteria decision making in the presence of multiple objectives. In this case the objectives being the four criteria. The objectives are usually conflicting and therefore, the proposed solution is highly dependent on the preferences of groups of decision makers and is developed within an understanding framework and mutual compromise. This paper presents a methodology using genetic algorithm and Fuzzy Analytical Hierarchy Process (Fuzzy AHP) at the product design stage in making decision based on the triple bottom line concept.